Using Write Pair Square Technique in Teaching Writing at Junior High School - Rizkiyuni Yuni Chaniago; Yetti Zainil (Universitas Negeri Padang, 2019)
ABSTRACTChaniago, Rizki Yuni. 2019. Using Write Pair Square Technique in Teaching Writing at Junior High SchoolThis paper discusses how to use Write Pair Square Technique in teaching writing at Junior High School. Based on the writers’ experience in teaching English, many students find the difficulties in teaching writing. Many students have difficulties in teaching writing, such as they lack of idea to write; they have less grammar; inappropriate technique when doing teaching and learning process. Write pair square is a cooperative learning that can motivate students in learning. The teacher divides the student for a small group of four that can be divided into pairs. In the first, each member in a group of four work individually to write answers. After that, students pair with a partners and share their work or answers. Then, two pairs of the foursome combine (squaring), and take turns to share and discuss what they had just thought or written. The team members try to help one another by giving comments to improve their works. By applying Write Pair Square Technique in teaching writing, the teacher can reach the goal of teaching writing to junior high school students. Keywords:Writing, Write Pair Square Technique